LVFRP: conducting sonar fish surveys in Lake Victoria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
William Kudoja explains how sonar technology is being used to assess the quantities of targeted fish species in Lake Victoria and is helping the authorities to set reasonable catch quotas.